Reduced Myocardial Flow in Heart Failure Patients With Preserved Ejection Fraction. (July 2016) - Srivaratharajah, Kajenny; Coutinho, Thais; deKemp, Robert; Liu, Peter; Haddad, Haissam; Stadnick, Ellamae; Davies, Ross A.; Chih, Sharon; Dwivedi, Girish; Guo, Ann; Wells, George A.; Bernick, Jordan; et al.
Abstract : Background—: There remains limited insight into the pathophysiology and therapeutic advances directed at improving prognosis for patients with heart failure with preserved ejection fraction (HFpEF). Recent studies have suggested a role for coronary microvascular dysfunction in HFpEF. Rb-82 cardiac positron emission tomography imaging is a noninvasive, quantitative approach to measuring myocardial flow reserve (MFR), a surrogate marker for coronary vascular health. The aim of this study was to determine whether abnormalities exist in MFR in patients with HFpEF without epicardial coronary artery disease. Methods and Results—: A total of 376 patients with ejection fraction ≥50%, no known history of obstructive coronary artery disease, and a confirmed diagnosis of heart failure (n=78) were compared with patients with no evidence of heart failure (n=298), further stratified into those with (n=186) and without (n=112) hypertension. Global and regional left ventricular MFR was calculated as stress/rest myocardial blood flow using Rb-82 positron emission tomography. Patients with HFpEF were more likely to be older, female, and have comorbid hypertension, diabetes mellitus, dyslipidemia, atrial fibrillation, anemia, and renal dysfunction. HFpEF was associated with a significant reduction in global MFR (2.16±0.69 in HFpEF versus 2.54±0.80 in hypertensive controls; P <0.02 and 2.89±0.70 in normotensive controls; P <0.001). A diagnosis of HFpEF was associated with 2.62 times greater unadjusted odds of having low global MFR (defined as <2.0) and remained a significant predictor of reduced global MFR after adjusting for comorbidities. Conclusions—: HFpEF, in the absence of known history for obstructive epicardial coronary artery disease, is associated with reduced MFR independent of other risk factors. Abstract : Supplemental Digital Content is available in the text.